Chemical and biological study of Croton species occurring in the Pernambuco Sertão: An integrative review (Research, Society and Development, 2024)
There are around 350 species of Croton in Brazil, with approximately 110 of them occurring in the Northeast region, particularly in Pernambuco. These species exhibit considerable chemical and biological diversity, which include several active compounds of great scientific interest. This review aims to map the chemical composition and biological activities of Croton species from backlands of Pernambuco. To achieve this, were conducted comprehensive searches for scientific articles in national and international databases- such as SciELO, Scopus, Science Direct, PubMed and Web of Science, using relevant keywords and Boolean operators. The Search focus on Croton species in backlands of Pernambuco over the past 10 years. The analysis identified 48 published articles, which examined both phytochemical characterization and biological activities of different Croton species, as well as these combined analyzes and in different applications for scientific and practical purposes. The studies also explored practical applications, such as the development of new medicines and herbal treatments. However, despite advancement on identification of new bioactive compounds and determining their pharmacological activities, there is notable gap in research on Croton species in Pernambuco. This represents a significant opportunity for further research, particularly in the field of phytochemical characterization and the discovery of novel biological activities within this genus.